Changes of vitamin D levels and bone turnover markers after CPAP therapy: a randomized sham‐controlled trial. (25th September 2017) - Theorell‐Haglöw, Jenny; Hoyos, Camilla M.; Phillips, Craig L.; Yee, Brendon J.; Herrmann, Markus; Brennan‐Speranza, Tara C.; Grunstein, Ronald R.; Liu, Peter Y.
Summary: The aim was to investigate whether continuous positive airway pressure treatment could modulate serum vitamin D (25‐hydroxyvitamin D) and bone turnover markers (collagen‐type 1 cross‐linked C‐telopeptide, osteocalcin and N‐terminal propeptide of type 1 collagen) in secondary analysis from a randomized controlled trial. Sixty‐five continuous positive airway pressure‐naïve male patients with obstructive sleep apnea (age = 49 ± 12 years, apnea–hypopnea index = 39.9 ± 17.7 events h −1, body mass index = 31.3 ± 5.2 kg m −2 ) were randomized to receive either real ( n = 34) or sham ( n = 31) continuous positive airway pressure for 12 weeks. At 12 weeks, all participants received real continuous positive airway pressure for an additional 12 weeks. After 12 weeks of continuous positive airway pressure (real versus sham), there were no between‐group differences for any of the main outcomes [Δ25‐hydroxyvitamin D: −0.80 ± 5.28 ng mL −1 (mean ± SE) versus 3.08 ± 3.66 ng mL −1, P = 0.42; Δcollagen‐type 1 cross‐linked C‐telopeptide: 0.011 ± 0.014 ng mL −1 versus −0.004 ± 0.009 ng mL −1, P = 0.48; Δosteocalcin: 1.13 ± 1.12 ng mL −1 versus 0.46 ± 0.75 ng mL −1, P = 0.80; ΔN‐terminal propeptide of type 1 collagen: 2.07 ± 3.05 μ g L −1 versus −1.05 ± 2.13 μ g L −1, P = 0.48]. There were no further differences in subgroup analyses (continuous positive airway pressure‐compliant patients, patients with severe obstructive sleep apnea or sleepy patients). However, after 24 weeks irrespective of initial randomization, vitamin D increased in patients with severe obstructive sleep apnea (9.56 ± 5.51 ng mL −1, P = 0.045) and in sleepy patients (14.0 ± 4.69 ng mL −1, P = 0.007). Also, there was a significant increase in osteocalcin at 24 weeks (3.27 ± 1.06 ng mL −1, P = 0.01) in compliant patients. We conclude that 12 weeks of continuous positive airway pressure did not modulate vitamin D or modulate any of the bone turnover markers compared with sham. However, it is plausible that continuous positive airway pressure may have late beneficial effects on vitamin D levels and bone turnover markers in selected groups of patients with obstructive sleep apnea.